Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.21894/jopr.2017.0003
|View full text |Cite
|
Sign up to set email alerts
|

DETACHED LEAF ASSAY FOR in vitro SCREENING OF POTENTIAL BIOCONTROL AGENTS TO CONTROL GOOSEGRASS WEED (Eleusine indica)

Abstract: Eleusine indica (goosegrass) is a hard to control tropical grass weed that thrives in open spaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The pathogenicity test using detached leaf assay, clearly demonstrated that P. caribaeo-quercicola INL3-2 does not pose a threat to the host plant, rather suggested a mutualistic or commensalistic relationship. This study is in line with the tendencies of similar non-pathogenic behaviors found in fungi associated with Eleusine indica reported by Maizatul-Suriza et al [36] The non-pathogenic nature of P. caribaeoquercicola raises intriguing possibilities about its role in the ecosystem particularly in its association with the medicinal plant and warrants further investigation. This discovery also opens up new possibilities for studying the potential for a symbiotic relationship of P. caribaeo-quercicola with its host plant I. racemosa, where the endophytic fungus might contribute to bring out the hidden potentials of host such as growth, nutrient uptake, phytohormone production, stress resistance of its host plant besides providing resistance against certain pathogens.…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…The pathogenicity test using detached leaf assay, clearly demonstrated that P. caribaeo-quercicola INL3-2 does not pose a threat to the host plant, rather suggested a mutualistic or commensalistic relationship. This study is in line with the tendencies of similar non-pathogenic behaviors found in fungi associated with Eleusine indica reported by Maizatul-Suriza et al [36] The non-pathogenic nature of P. caribaeoquercicola raises intriguing possibilities about its role in the ecosystem particularly in its association with the medicinal plant and warrants further investigation. This discovery also opens up new possibilities for studying the potential for a symbiotic relationship of P. caribaeo-quercicola with its host plant I. racemosa, where the endophytic fungus might contribute to bring out the hidden potentials of host such as growth, nutrient uptake, phytohormone production, stress resistance of its host plant besides providing resistance against certain pathogens.…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…Pada 2010-2011, beberapa perusahaan kelapa sawit Indonesia membentuk konsorsium untuk melakukan introduksi populasi wild dari Angola, Afrika bagian barat daya. Populasi kelapa sawit tipe wild dari Angola merupakan salah satu populasi yang diintroduksi ke Indonesia dimana karakter-karakter yang dimiliki hingga saat ini perlu diekplorasi lebih lanjut, baik karakter fenotipe maupun genotipe (Arias et al, 2013;Ong et al, 2018;Sujadi et al, 2019). Tujuan lain dari introduksi ini antara lain untuk memperluas keragaman genetik pada populasi program pemuliaan yang telah Abstrak -Introduksi populasi dari luar ke dalam suatu program pemuliaan kelapa sawit diperlukan untuk meningkatkan keragaman genetik populasi yang telah ada sebelumnya.…”
Section: Pendahuluanunclassified
“…The putative Bipolaris bicolor was isolated from diseased E. indica plants based on the modified method of Maizatul-Suriza et al (2017). Leaf samples of E. indica infected with leaf spot disease were collected 4 meters apart from each other in corn fields at Research Farm, Bukit Kor campus, University of Malaysia Terengganu.…”
Section: Isolation Of Putative Bipolaris Bicolormentioning
confidence: 99%
“…Bipolaris setariae, Pyricularia grisea (Figliola et al 1988), Phoma herbarum and Bipolaris sorokiniana (Maizatul-Suriza et al 2017) and Bipolaris bicolor have all been isolated from diseased E. indica (Fakri et al 2019). Pathogenicity tests revealed that Bipolaris sorokiniana infected E. indica on day five after artificial inoculation and had the highest disease severity as compared to P. herbarum and C. aeria after 40 days of treatment (Ismail et al 2020), none of these fungal pathogens, however, have been evaluated in conjunction with herbicides to combat E. indica.…”
Section: Introductionmentioning
confidence: 99%